c.2 - "Nag Chaudhuri, B. D." (Simla, 1979)
These chapters are in substance a series of six lectures deli vered at the Indian Institute of Advanced Study at Simla in May 1977 as visiting professor. Professor S.C. Dube's invita tion to deliver the lectures gave me an opportunity to look at the interaction between society and technology in the perspec tive of man's social evolution. The interest grew out of a desire to follow the evolution of technology in the early years of hominoid evolution. The lectures start with the question whether social evolution is purely a series of technological and geographical accidents or whether technology has a pervasive role in the social evolution of man and perhaps also in the biological evolution of man from the hominoids. The variety and intimacy of the relation between technology and several social institutions is explored. Finally, some tentative conclusions and issues are noted.
Keywords: Technology - Social aspects